District Capacity Revitalization for Strengthening Administration of Traditional Villages in Jayapura District: A Mixed Method Approach - Muhdiarta, Untung; Silo, Akbar; Hafizrianda, Yundi; Situmorang, Hotnida Erlin (KnE Social Sciences, 2024)
This study aimed to challenge the strengthening of regional governance in Jayapura District, particularly focusing on the administration of traditional villages. It aligns legislative initiatives aiming to enhance governance through community empowerment and nurturing local wisdom, despite existing challenges in effective governance and development outcomes. The primary objective is to create a comprehensive framework for District Capacity Building in Village Administration. Employing a mixedmethod approach, the study combines quantitative data from structured surveys with qualitative data from FGD. Purposive sampling targets government officials and community leaders, ensuring data relevance. Statistical analysis of survey data provides a baseline understanding of district capacity, while FGDs offer in-depth insights into specific challenges and dynamics. The research introduces a refined district capacity strengthening model using the Treaming Theory, indicating indirect influences of funding, district capacity, and infrastructure on district head duties and functions through district authority. This model underscores the need for increased district authority, supported by improved funding and infrastructure, to enhance traditional village development effectively. The study reveals that revitalizing district roles as development centers and traditional village development districts can significantly improve regional governance in Jayapura District and provide recommendations for policy formulation, strengthening implementation of district functions, and enhancing traditional village governance. Keywords: district authority, government management, traditional villages